Analisis Potensi Bahan Pakan Lokal Untuk Pengembangan Ternak Sapi Potong di Sumatera Barat - F. Madarisa; l. Iskandar; Deswita Andelina (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2007)
Using secondary data, a survey was conducted to assess the availability of potentially beef cattle feed in West Sumatra province. Two methods were applied to analye the collected data; 1) supporting capacity index (IDD) developed by Livestock Research Institute at Ciawi Bogor which also legally accepted as an instrument to determine regional capacity in supporting cattle feed. 2). Nell and Rollinson method which has been applied in Indonesia since 1974 supported by UNDP. Results showed that by the first method (IDD), West Sumatra has 1,888,032.77 ton and 459,041,026 ton potential feed from agriculture and agricultural by products respectively in 2007. The second Nell and Rollinson method confirmed that West Sumatra has 33,286,255,20 ton from grass production and 588,638.72 ton agricultural by products. Compared between the West Sumatra regional capacity to support beef cattle as 1,028,935.9 animal unit, and ruminants population as 446,072.7 animal unit, there is an additional capacity to keep ruminants as 562,863.2 animal unit. Based on the cattle contribution as 63 % to total population, West Sumatra could increase its support to cattle population by 355,110.6 animal unit. Nell and Rollinson showed an optimistic figure, namely 1,408,892 animal unit for cattle.